Architecture and Faux-nationalism: reflections on a remark made by the British architectural historian Gavin Stamp about the German-American architect Ludwig Mies van der Rohe. Issue 4 (7th August 2020) - Watson, Victoria
ABSTRACT: This is a short 'think-piece', it was prompted by my visit to the RIBA exhibition Mies van der Rohe & James Stirling: Circling the Square, where I came across a letter, dated 1985, from the architectural historian Gavin Stamp to Margaret Thatcher. Stamp was concerned about an architectural proposal for a site in the City of London by the Avant-garde, modernist architect Ludwig Mies van der Rohe. As a long-term observer of the British reception of Mies, the contents and circumstances of the letter got me thinking.